Answer: sale 90
Step-by-step explanation:
Answer:
The reasonable estimate for the solution is (2.29, -4.87)
Step-by-step explanation:
The reasonable estimate for the solution is the point where the two lines intersect each other.
To get the point where they intersect, we will simply equate the system of equations given as shown:
![-3x+2=\frac{1}{2}x-6\\Collect \ the \ like \ terms\\-3x-\frac{1}{2}x=-6-2\\\frac{-7x}{2}=-8\\-7x=-16\\x=\frac{16}{7} \\x=2.29](https://tex.z-dn.net/?f=-3x%2B2%3D%5Cfrac%7B1%7D%7B2%7Dx-6%5C%5CCollect%20%5C%20the%20%5C%20like%20%5C%20terms%5C%5C-3x-%5Cfrac%7B1%7D%7B2%7Dx%3D-6-2%5C%5C%5Cfrac%7B-7x%7D%7B2%7D%3D-8%5C%5C-7x%3D-16%5C%5Cx%3D%5Cfrac%7B16%7D%7B7%7D%20%20%20%20%5C%5Cx%3D2.29)
Substitute x = 2.29 into any of the equation
Using the equation y = -3x+2
y = -3(2.29)+2
y = -6.87+2
y =-4.87
This shows that the reasonable estimate for the solution is (2.29, -4.87)
Further explanation on the similar question can be found here brainly.com/question/19713330
-7 because 56 divided by 8 is 7 but since we are using division with negatives and positives a positive + a negative = a negative
so your answer is -7
hope this helps hope i m brainliest i need 3 more
Answer:
B
Step-by-step explanation:
They help support the tree in shallow soil so it does not fall over
Answer:
y=1
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
6=2(y+2)
6=(2)(y)+(2)(2)(Distribute)
6=2y+4
Step 2: Flip the equation.
2y+4=6
Step 3: Subtract 4 from both sides.
2y+4−4=6−4
2y=2
Step 4: Divide both sides by 2.
2y/2 2/2